An eye-tracking study of bilinguals’ processing of lexical cues in L1 and L2 / Irwan Tham Adam Tham - Irwan Tham, Adam Tham (2016)
The purpose of this study was to examine how bilinguals process texts with lexical cues in their first language (L1) and second language (L2) using eye-tracking methodology. This study was conducted by obtaining quantitative data from an eye-tracker as well as a post-test. Qualitative data was also obtained to supplement the quantitative analysis through interviews with participants. The findings from the eye-tracking results indicated that participants’ fixations were similar on novel words accompanied by their L1 cues and those accompanied by their L2 cues. When comparing participants’ fixation on L1 and L2 cues, the findings showed that participants spent similar time fixating on both types of cues. Finally, the use of L1 cues leads to similar amount of acquisition of novel words compared to the use of L2 cues. The findings provided three contributions towards research in language learning. First, the use of the eye-tracking methodology is discussed along with how it may be triangulated to existing methodologies for studying language processing. Second, the study provided insights on how bilinguals process cues in L1 and L2. Third, the effectiveness of using cues in L1 and L2 towards incidental vocabulary acquisition was captured under a similar context. The results provided additional insights on the nature of bilinguals. The findings of this research will be useful towards teachers as well as students to develop an alternative view of bilinguals as well as shedding light on the way bilinguals process text.